2017
DOI: 10.1002/slct.201601443
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Graphene like Carbon Nanosheet: Interaction with some Drug Molecules and Anticancer Activity

Abstract: Graphene‐like carbon nano‐sheets are prepared from dextrin, with cetyltrimethyl ammonium bromide (CTAB) as stabiliser, by the action of concentrated sulfuric acid. Oxidation of such sheets produce graphene oxide (GO) like material. These are characterized in the usual manner and their photophysical properties are explored. Binding of certain drug molecules with carbon nano‐sheet is investigated fluorimetrically. Finally, action of carbon nano‐sheets on normal and cancer cell lines revealed that the sheets have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Each material has its own unique texture due to its own unique structure, just like the touch, color, and performance we just mentioned. Various types of textile materials have different texture effects due to different raw fibers, weaving methods, and finishing [15]. e composition of different materials is to connect with each other in the difference of the characteristics of different materials so as to give people a strong contrast in the sense of the material.…”
Section: Composition Of Traditionalmentioning
confidence: 99%
“…Each material has its own unique texture due to its own unique structure, just like the touch, color, and performance we just mentioned. Various types of textile materials have different texture effects due to different raw fibers, weaving methods, and finishing [15]. e composition of different materials is to connect with each other in the difference of the characteristics of different materials so as to give people a strong contrast in the sense of the material.…”
Section: Composition Of Traditionalmentioning
confidence: 99%
“…Investigators have developed metal, metal oxides and polymeric structures as anticancer agents. ZnO/TiO 2 , Au and poly(glycidyl methacrylate) among the nanostructure materials were used as an anticancer agent towards MCF‐7 cell lines. Here, i‐ZANF was better against human breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation of such sheets produces GO like materials. The results showed that carbon nano-sheets have no effect on normal cells, but induced apoptosis on cancer cells [ 138 ]. In the investigation of Li and Xiang et al, soybean phospholipid-encapsulated MoS 2 (SP–MoS 2 ) nanosheets were successfully synthesized in a rotary evaporator.…”
Section: Encapsulation Of 2d Materialsmentioning
confidence: 99%
“… N.A. anticancer anticancer [ 138 ] MoS 2 Liposomes Light antitumor 4T1 [ 139 ] GO Polymer pH antitumor Hela cells [ 125 ] BP Polymer Light anticancer MCF7 breast tumor [ 165 ] MnO2 Aptamer Magnetic field antitumor N.A. MnO2 glucose oxidase Light &Magnetic field antitumor A375 tumor GO Hydrogel Magnetic field antitumor S 180 tumor [ 140 ] GO Hydrogels N.A.…”
Section: The Field Of 2d Materials Sddss Therapymentioning
confidence: 99%